5.2.51 Problems 5001 to 5100

Table 5.269: Second order linear ODE

#

ODE

Mathematica

Maple

17157

\[ {}x y^{\prime \prime }-\left (2 x^{2}+1\right ) y^{\prime } = 4 x^{3} {\mathrm e}^{x^{2}} \]

17158

\[ {}y^{\prime \prime }-2 \tan \left (x \right ) y^{\prime } = 1 \]

17159

\[ {}x \ln \left (x \right ) y^{\prime \prime }-y^{\prime } = \ln \left (x \right )^{2} \]

17160

\[ {}x y^{\prime \prime }+\left (2 x -1\right ) y^{\prime } = -4 x^{2} \]

17161

\[ {}y^{\prime \prime }+\tan \left (x \right ) y^{\prime } = \cos \left (x \right ) \cot \left (x \right ) \]

17162

\[ {}4 x y^{\prime \prime }+2 y^{\prime }+y = 1 \]

17163

\[ {}4 x y^{\prime \prime }+2 y^{\prime }+y = \frac {6+x}{x^{2}} \]

17164

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }+2 x y^{\prime } = \frac {1}{x^{2}+1} \]

17165

\[ {}\left (1-x \right ) y^{\prime \prime }+x y^{\prime }-y = \left (x -1\right )^{2} {\mathrm e}^{x} \]

17166

\[ {}2 x^{2} \left (2-\ln \left (x \right )\right ) y^{\prime \prime }+x \left (4-\ln \left (x \right )\right ) y^{\prime }-y = \frac {\left (2-\ln \left (x \right )\right )^{2}}{\sqrt {x}} \]

17167

\[ {}y^{\prime \prime }+\frac {2 y^{\prime }}{x}-y = 4 \,{\mathrm e}^{x} \]

17168

\[ {}x^{3} \left (-1+\ln \left (x \right )\right ) y^{\prime \prime }-x^{2} y^{\prime }+x y = 2 \ln \left (x \right ) \]

17169

\[ {}\left (x^{2}-2 x \right ) y^{\prime \prime }+\left (-x^{2}+2\right ) y^{\prime }-2 \left (1-x \right ) y = 2 x -2 \]

17170

\[ {}x^{\prime \prime }+x^{\prime }+x = 0 \]

17171

\[ {}x^{\prime \prime }+2 x^{\prime }+6 x = 0 \]

17172

\[ {}x^{\prime \prime }+2 x^{\prime }+x = 0 \]

17180

\[ {}y^{\prime \prime }+\lambda y = 0 \]

17181

\[ {}y^{\prime \prime }+\lambda y = 0 \]

17182

\[ {}y^{\prime \prime }-y = 0 \]

17183

\[ {}y^{\prime \prime }+y = 0 \]

17185

\[ {}y^{\prime \prime }+y = 0 \]

17186

\[ {}y^{\prime \prime }-y = 0 \]

17187

\[ {}y^{\prime \prime }-2 y^{\prime }+2 y = 0 \]

17188

\[ {}y^{\prime \prime }+\alpha y^{\prime } = 0 \]

17189

\[ {}y^{\prime \prime }+\alpha ^{2} y = 1 \]

17190

\[ {}y^{\prime \prime }+y = 1 \]

17191

\[ {}y^{\prime \prime }+\lambda ^{2} y = 0 \]

17192

\[ {}y^{\prime \prime }+\lambda ^{2} y = 0 \]

17195

\[ {}x y^{\prime \prime }+y^{\prime } = 0 \]

17216

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (4 x^{2}-\frac {1}{9}\right ) y = 0 \]

17217

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {1}{4}\right ) y = 0 \]

17218

\[ {}y^{\prime \prime }+\frac {y^{\prime }}{x}+\frac {y}{9} = 0 \]

17219

\[ {}y^{\prime \prime }+\frac {y^{\prime }}{x}+4 y = 0 \]

17220

\[ {}x^{2} y^{\prime \prime }-2 x y^{\prime }+4 \left (x^{4}-1\right ) y = 0 \]

17221

\[ {}x y^{\prime \prime }+\frac {y^{\prime }}{2}+\frac {y}{4} = 0 \]

17222

\[ {}y^{\prime \prime }+\frac {5 y^{\prime }}{x}+y = 0 \]

17223

\[ {}y^{\prime \prime }+\frac {3 y^{\prime }}{x}+4 y = 0 \]

17224

\[ {}y^{\prime \prime }+4 y = \cos \left (x \right )^{2} \]

17225

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = \pi ^{2}-x^{2} \]

17226

\[ {}y^{\prime \prime }-4 y = \cos \left (\pi x \right ) \]

17227

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = \arcsin \left (\sin \left (x \right )\right ) \]

17228

\[ {}y^{\prime \prime }+9 y = \sin \left (x \right )^{3} \]

17288

\[ {}x^{\prime \prime } = 0 \]

17289

\[ {}x^{\prime \prime } = 1 \]

17290

\[ {}x^{\prime \prime } = \cos \left (t \right ) \]

17291

\[ {}x^{\prime \prime }+x^{\prime } = 0 \]

17292

\[ {}x^{\prime \prime }+x^{\prime } = 0 \]

17293

\[ {}x^{\prime \prime }-x^{\prime } = 1 \]

17294

\[ {}x^{\prime \prime }+x = t \]

17295

\[ {}x^{\prime \prime }+6 x^{\prime } = 12 t +2 \]

17296

\[ {}x^{\prime \prime }-2 x^{\prime }+2 x = 2 \]

17297

\[ {}x^{\prime \prime }+4 x^{\prime }+4 x = 4 \]

17298

\[ {}2 x^{\prime \prime }-2 x^{\prime } = \left (t +1\right ) {\mathrm e}^{t} \]

17299

\[ {}x^{\prime \prime }+x = 2 \cos \left (t \right ) \]

17545

\[ {}y^{\prime \prime }+t y = 0 \]

17547

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+\alpha \left (\alpha +1\right ) y = 0 \]

17548

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (-\nu ^{2}+x^{2}\right ) y = 0 \]

17550

\[ {}y^{\prime \prime }-t y = \frac {1}{\pi } \]

17551

\[ {}a \,x^{2} y^{\prime \prime }+b x y^{\prime }+c y = d \]

17552

\[ {}y^{\prime \prime }+y = 0 \]

17553

\[ {}y^{\prime \prime }+9 y = 0 \]

17554

\[ {}y^{\prime \prime }+y^{\prime }+16 y = 0 \]

17555

\[ {}y^{\prime \prime }+3 y^{\prime }+4 y = 0 \]

17556

\[ {}y^{\prime \prime }-y^{\prime }+4 y = 0 \]

17557

\[ {}t y^{\prime \prime }+3 y = t \]

17558

\[ {}\left (t -1\right ) y^{\prime \prime }-3 t y^{\prime }+4 y = \sin \left (t \right ) \]

17559

\[ {}t \left (t -4\right ) y^{\prime \prime }+3 t y^{\prime }+4 y = 2 \]

17560

\[ {}y^{\prime \prime }+\cos \left (t \right ) y^{\prime }+3 \ln \left (t \right ) y = 0 \]

17561

\[ {}\left (x +3\right ) y^{\prime \prime }+x y^{\prime }+y \ln \left (x \right ) = 0 \]

17562

\[ {}\left (x -2\right ) y^{\prime \prime }+y^{\prime }+\left (x -2\right ) \tan \left (x \right ) y = 0 \]

17563

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+\frac {\alpha \left (\alpha +1\right ) \mu ^{2} y}{-x^{2}+1} = 0 \]

17565

\[ {}t^{2} y^{\prime \prime }-2 y = 0 \]

17567

\[ {}y^{\prime \prime }+4 y = 0 \]

17568

\[ {}y^{\prime \prime }-2 y^{\prime }+y = 0 \]

17569

\[ {}x^{2} y^{\prime \prime }-x \left (x +2\right ) y^{\prime }+\left (x +2\right ) y = 0 \]

17570

\[ {}\left (1-x \cot \left (x \right )\right ) y^{\prime \prime }-x y^{\prime }+y = 0 \]

17571

\[ {}y^{\prime \prime }-y^{\prime }-2 y = 0 \]

17572

\[ {}a y^{\prime \prime }+b y^{\prime }+c y = 0 \]

17573

\[ {}t^{2} y^{\prime \prime }-4 t y^{\prime }+6 y = 0 \]

17574

\[ {}t^{2} y^{\prime \prime }+2 t y^{\prime }-2 y = 0 \]

17575

\[ {}t^{2} y^{\prime \prime }+3 t y^{\prime }+y = 0 \]

17576

\[ {}t^{2} y^{\prime \prime }-t \left (2+t \right ) y^{\prime }+\left (2+t \right ) y = 0 \]

17577

\[ {}x y^{\prime \prime }-y^{\prime }+4 x^{3} y = 0 \]

17578

\[ {}\left (x -1\right ) y^{\prime \prime }-x y^{\prime }+y = 0 \]

17579

\[ {}x^{2} y^{\prime \prime }-\left (x -\frac {3}{16}\right ) y = 0 \]

17580

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {1}{4}\right ) y = 0 \]

17581

\[ {}x y^{\prime \prime }-\left (x +n \right ) y^{\prime }+n y = 0 \]

17582

\[ {}y^{\prime \prime }+a \left (x y^{\prime }+y\right ) = 0 \]

17583

\[ {}y^{\prime \prime }+2 y^{\prime }-3 y = 0 \]

17584

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = 0 \]

17585

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = 0 \]

17586

\[ {}9 y^{\prime \prime }+6 y^{\prime }+y = 0 \]

17587

\[ {}y^{\prime \prime }-2 y^{\prime }+2 y = 0 \]

17588

\[ {}y^{\prime \prime }-2 y^{\prime }+6 y = 0 \]

17589

\[ {}4 y^{\prime \prime }-4 y^{\prime }+y = 0 \]

17590

\[ {}2 y^{\prime \prime }-3 y^{\prime }+y = 0 \]

17591

\[ {}6 y^{\prime \prime }-y^{\prime }-y = 0 \]

17592

\[ {}9 y^{\prime \prime }+12 y^{\prime }+4 y = 0 \]

17593

\[ {}y^{\prime \prime }+2 y^{\prime }-8 y = 0 \]

17594

\[ {}y^{\prime \prime }+2 y^{\prime }+2 y = 0 \]